Reprocessing with orthopedic surgery instrument in a material and sterilization center (Research, Society and Development, 2021)
Objective: To analyze the causes of reprocessing due to non-conformities of orthopedic surgery instruments in a Material and Sterilization Center (CME). Method: This was a descriptive exploratory, retrospective study with a quantitative approach, developed in a class II MSC, based on the service reprocessing notification book and notifications from the VIGIHOSP Risk Management and Patient Safety software. Results: From the identification of the number of repetitions of each non-conformity in specific boxes, it was possible to see that the loss of packaging integrity is the main cause of rework. Conclusion: The most reprocessed orthopedic surgery boxes are in accordance with the guidelines recommended, however, compliance is not preventing the loss of packaging integrity.